An overview of major role players regarding the Protection of State Information Bill: The case of the Right2Know Campaign, the South African National Editors' Forum and the African National Congress - Mnguni, Isaack Thamba (My University, 2015)
The fight against the Protection of State Information Bill (POSIB) by the Right2Know Campaign (R2K) and the South African National Editors’ Forum (Sanef) marks a key point in the fight to protect constitutional democracy in South Africa. Apart from undermining this constitutional democracy, the POSIB signals the extent of the ideological divide between the ruling party – the African National Congress (ANC) – and its opponents. This study suggests that the POSIB is a tool to serve the ideological and hegemonic interests of the ANC and its elites, shielding the party from scrutiny by the commercial press and other critical actors. In exploring the ideological discourse of the POSIB, this study uses semi-structured interviews conducted via email with members of the R2K and Sanef. The ANC chose not to participate in the study, but advised that its views were expressed on its party and Parliamentary websites. The study is intended to contribute to the academic literature on the media, primarily the press, and democracy in South Africa and to add insight into the current debates around the POSIB. Literature and theory agree that the flow and access to information is crucial for any democracy and any failure or blockage of this flow and access hinders democracy. However, this study finds that both Sanef and the R2K are also ideological actors. Both organisations use their position of opposition to the proposed legislation to further their own ideological interests. The position of Sanef reflects its journalistic interests and the forum’s own definition of the role of the press, including the concept of press freedom. The study finds that the R2K is also an ideological actor and uses its opposition to the POSIB to promote and widen discourse on the concept of “public interest.”
A dissertation submitted to the Faculty of Humanities, University of Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Arts in Media Studies. September, 2014